Written Assessment in Medical Education - Gasmalla, Hosam Eldeen Elsadig; Ibrahim, Alaa AbuElgasim Mohamed; Wadi, Majed M.; Taha, Mohamed H. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book is an indispensable yet simple reference for the daily use of a medical teacher. It addresses the needs of medical teachers interested in providing instruction and assessment in writing and written language, offering detailed guidance in simple and straightforward language. The book goes beyond mere description; it provides many practical examples, valuable materials that can be utilized in training workshops and medical educator professional development courses. The book will be of interest to novice and experienced teachers in medical schools, in addition to university teachers in other health professions, such as dentistry, pharmacy, nursing, medical laboratory, physiotherapy, biomedical engineering and veterinary medicine.
Chapter 1. Basic concepts -- Chapter 2. Assessment of learning outcomes -- Chapter 3. Blueprint in Assessment -- Chapter 4. Types of Written -- Chapter 5. open-response questions -- Chapter 6. MCQs (A-Type) -- Chapter 7. MCQs (R-type) -- Chapter 8. Standard Setting -- Chapter 9. Online Assessment.
Keywords: Medical education; Educational tests and measurements; Medical Education; Assessment and Testing